Research on capacity planning and optimization of regional integrated energy system based on hybrid energy storage system. (5th November 2020) - Wang, Yongli; Song, Fuhao; Ma, Yuze; Zhang, Yuli; Yang, Jiale; Liu, Yang; Zhang, Fuwei; Zhu, Jinrong
Highlights: An expansion planning model of hybrid energy storage is proposed. Stabilizing fluctuations and demand response functions are considered. Wavelet packet decomposition is used to achieve fluctuation stability. A statistical model for the life of the energy storage system is proposed. Abstract: Some regional integrated energy systems (RIES) have installed equipments such as wind turbine and photovoltaic, but the fluctuation of these intermittent power supply is large, resulting in a certain amount of energy waste. Because energy storage can improve the utilization rate of renewable energy, this paper establishes a storage capacity expansion planning model considering multiple functions of hybrid energy storage in the RIES. In this model, the wavelet packet decomposition method is used to reasonably decompose the high-frequency fluctuation and low-frequency fluctuation of renewable energy to achieve the function of stabilizing fluctuation. Meanwhile, an operation strategy for hybrid energy storage to participate in demand response is proposed. Rain flow counting method is used to research the life of hybrid energy storage system, which improves the accuracy of energy storage annual cost calculation. In the Simulation and Analysis section, the genetic quantum algorithm is used for simulation and analysis of the role and benefits of hybrid energy storage. The simulation results show that the benefit of hybrid energy storage in capacity expansion construction is increased by 10.4%, and when the electricity and gas prices fluctuate by ±20%, the hybrid energy storage configuration proposed in this paper has a stable advantage in more than 95%.